Disability, Elternschaft und Soziale Arbeit Zur Bedeutung von Zuschreibungen, Fremdwahrnehmungen und Selbstverständnissen für Eltern mit Lernschwierigkeiten - More, Rahel (Schriftenreihe der ÖFEB-Sektion Sozialpädagogik, 2021)
This book deals with parenthood of mothers and fathers with so-called learning difficulties, who are often confronted with prejudices about their abilities in the role of parents, in Austria. The author is oriented towards the social critique of disability studies and follows an emancipatory-participatory approach. The relevance of multidimensional disadvantages and the respective (non-) existing framework conditions for the perception of the parental role are listed as central results.